1, 3, 2-Diazaborole-derived carbene complexes of boron. Issue 1 (23rd November 2017) - Hickox, Hunter P.; Wang, Yuzhong; Luedecke, Kaitlin M.; Xie, Yaoming; Wei, Pingrong; Carrillo, Deidrah; Dominique, Nathaniel L.; Cui, Dongtao; Schaefer, Henry F.; Robinson, Gregory H.
Abstract : 1, 3, 2-Diazaborole-derived carbene complexes of boron were synthesized via 1, 2-hydrogen migration. Abstract : Reaction of 2-bromo-1, 3, 2-diazaborole (1 ) with excess BBr3 induces 1, 2-hydrogen migration, giving 1, 3, 2-diazaborole-derived carbene complexes of boron bromide (2 ). Compound2 exists in a dynamic solution equilibrium with1 . The 1 H NMR study shows that the equilibrium lies to the right side of the dissociation reaction of2 . Parallel reaction of1 with excess BI3 gives the corresponding 1, 3, 2-diazaborole-derived carbene boron iodide complex (3 ). Notably, in contrast to2, the dissociation reaction of3 largely lies to the left side, favouring the formation of3 . The dynamic solution equilibrium behaviours of2 and3 are probed by both experimental and theoretical methods.